Essays in applied microeconomics: behaviour and well-being - Milligan, J; Toussaert, S (2021)
This thesis explores challenges related to measuring well-being and behaviour, presents novel ways to handle such data and offers some evidence from analysing these types of data which has implications for welfare. Across the three chapters I have two main objectives. Firstly, I present and justify methods to handle data on unobservable feelings, such as satisfaction, motivation or pride. Secondly, the research questions are connected through their preoccupations with understanding human welfare.